Evaluation of deep eutectic solvents for the extraction of fucoxanthin from the alga Tisochrysis lutea – COSMO-RS screening and experimental validation. Issue 5 (October 2022) - Xu, Dingmeng; Chow, Jane; Weber, Cameron C.; Packer, Michael A.; Baroutian, Saeid; Shahbaz, Kaveh
Abstract: Fucoxanthin is a carotenoid in algae with purported beneficial health-related properties including antioxidant, anti-photoaging, anti-metastasis, anti-hypertensive activity and more. These properties give fucoxanthin the potential to be used in cosmetic, dietary, and medicinal applications. This study evaluates the use of deep eutectic solvents (DESs) to extract fucoxanthin from the microalgae Tisochrysis lutea . Conductor-like Screening Model for Real Solvents (COSMO-RS) was used to screen the performance of 24 different types of DESs in the extraction of fucoxanthin based on their calculated capacities. Experimental extraction validation was then carried out using the 6 top-ranked DESs. The experimental results revealed that the extraction capacity of the thymol: dodecanoic acid DES (1.25: 1 molar ratio) for fucoxanthin was the most efficient (7.69 mg/g dry biomass weight (DW)) among the DESs explored under the screening conditions and was higher than the capacity of the conventional solvents methanol (6.29 mg/g DW) and ethanol (6.75 mg/g DW). This corresponded with COSMO-RS screening results. Then, the optimisation of extraction conditions for fucoxanthin using thymol: dodecanoic acid DES was further investigated, revealing that the highest yield of fucoxanthin (22.03 mg/g DW) was extracted at optimum experimental conditions at a temperature of 36.2 °C, stirring time of 2.58 h, and the biomass percentage of 11.36 %. Additionally, fucoxanthin showed good stability in thymol: dodecanoic acid DES over eleven days of storage. After seven extraction cycles, the final fucoxanthin concentration (13.06 mg/mL DES) resulted in a good reusability of the terpene-based food safe DES. Graphical Abstract: Thymol: dodecanoic acid DES (1.25:1 mola ratio) showed the highest extraction efficiency of fucoxanthin from the Alga Tisochrysis lutea. ga1 Highlights: COSMO-RS screened the performance of 24 DESs for fucoxanthin extraction. The screening results were validated experimentally for 6 top-ranked DESs. Thymol: dodecanoic acid DES resulted in the highest fucoxanthin extraction yields. The σ-profile and σ-potential revealed a possible fucoxanthin extraction mechanism. Fucoxanthin extraction yields of 22.03 mg/g DW were obtained under optimal condition.